Narasi Kuasa Konten Homoseksual di Media Sosial “Wattpad” - Zafirah Quroatun 'Uyun; Ariza Qurrata A'yun; Wiranda Rasnika (Jurnal Ilmu Komunikasi, 2021)
In the spread of homosexual content on social media platform Wattpad, there is fujoshi community that already exists in Indonesia. The fujoshi community provides homosexual content and making it legal to enjoy it. The purpose of this study is to find out fujoshi homosexual narrative in Indonesia using Wattpad. This research uses discourse analysis method. The results showed that the homosexual narrative built by fujoshi on Wattpad is unique, using other terms from Japanese (yaoi, uke, seme) and English (Boys Love, BL, and M-Preg) in order to be unrecognized by legal censors. The propagator of this content is the opposite sex of homosexuals, namely women, through imagination and fantasy, which is expressed in the form of images and writings. In addition, texts are produced and distributed based on favorite idol pairs. Although it is not produced every day, fanfiction is produced after receiving feedback in the form of fanservice from their idol couples. After being produced, fanfiction is distributed through Wattpad and notified to consumers (readers) through notifications which can be accessed completely freely.